2018
DOI: 10.1038/s41598-018-25764-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology of Shigella in the United Kingdom shows transmission of pathogen sublineages and determinants of antimicrobial resistance

Abstract: Shigella are globally important diarrhoeal pathogens that are endemic in low-to-middle income nations and also occur in high income nations, typically in travellers or community-based risk-groups. Shigella phylogenetics reveals population structures that are more reliable than those built with traditional typing methods, and has identified sublineages associated with specific geographical regions or patient groups. Genomic analyses reveal temporal increases in Shigella antimicrobial resistance (AMR) gene conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 30 publications
5
78
0
Order By: Relevance
“…For example, when applied to surveillance of Shiga toxin‐producing Escherichia coli serotype O157, whole genome sequencing detected twice as many disease clusters than traditional typing methods, including common source outbreaks that were geographically distributed across the country . Similarly, routine whole genome sequencing of Salmonella enterica and Shigella isolates in England and Wales has generated a rich repository of genomic data, providing unparalleled levels of strain discrimination and a wealth of information on the emergence and spread of antimicrobial‐resistant pathogens …”
Section: Whole Genome Sequencing: International Successesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when applied to surveillance of Shiga toxin‐producing Escherichia coli serotype O157, whole genome sequencing detected twice as many disease clusters than traditional typing methods, including common source outbreaks that were geographically distributed across the country . Similarly, routine whole genome sequencing of Salmonella enterica and Shigella isolates in England and Wales has generated a rich repository of genomic data, providing unparalleled levels of strain discrimination and a wealth of information on the emergence and spread of antimicrobial‐resistant pathogens …”
Section: Whole Genome Sequencing: International Successesmentioning
confidence: 99%
“…8 Similarly, routine whole genome sequencing of Salmonella enterica and Shigella isolates in England and Wales has generated a rich repository of genomic data, providing unparalleled levels of strain discrimination and a wealth of information on the emergence and spread of antimicrobial-resistant pathogens. 9,10…”
Section: Whole Genome Sequencing: International Successesmentioning
confidence: 99%
“…Genome-derived serotyping and AMR-conferring genes and SNPs was performed using the GeneFinder tool (https://github.com/phe-bioinformatics/gene_finder) [21,28]. Resistance to streptomycin, tetracycline, the sulphonamides and trimethoprim in Shigella species is high, and trends have been consistent for many years [5,[15][16][17]28]. We therefore focused our AMR analysis on the presence of genomic makers of resistance to macrolides (specifically ermB and mphA) and fluroquinolones (specifically mutations in the quinolones resistance determining regions (QRDR) of gyrA and parC), as the trends in resistance to these clinically relevant classes of antimicrobials fluctuated during the study period (data not shown).…”
Section: Whole Genome Sequencingmentioning
confidence: 99%
“…Whole genome sequencing (WGS) studies have been used to determine factors driving the emergence and transmission of Shigella spp. and have demonstrated that certain community outbreaks of shigellosis in the UK belonged to prolonged, global epidemics [5,[15][16][17][18]. These analysis have shown that lineages of S. flexneri serotypes 3a and 2a have exhibited intercontinental spread via sexual transmission in GBMSM networks, and subsequently acquired multiple antimicrobial resistance (AMR) determinants [5,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation